Translation, Adaptation, and Validation of Player Experience of Need Satisfaction Scale (PENS) Modified Version in Malaysian Multiplayer Online Battle Arena (MOBA) Players - T'ng, Soo Ting, Dr; Ho, Khee Hoong; Leong, Wen Sam; Siah, Poh Chua; Abdul Jalil, Nurul Iman Binti; Pau, Kee (UI Scholars Hub, 2025)
This study aimed to translate, adapt, and validate the modified version of the Player Experience of Need Satisfaction (PENS) for Malaysian Multiplayer Online Battle Arena (MOBA) players. The translation and adaptation process involved a rigorous procedure with nine mental health and linguistic experts. A non-probability sampling method was applied by recruiting 491 participants from the MOBA Facebook groups. The parallel analysis indicated a two-factor structure (autonomy and competence as one factor and relatedness as another factor). Confirmatory factor analysis demonstrated a better model fit for the translated version compared with the original English version, with satisfactory psychometric properties. Future studies should address psychometric concerns and evaluate the scale across diverse populations and game genres. This study provides a foundation for understanding and enhancing the gaming experience in the dynamic and rapidly growing mobile game aggregation market.